Understanding Digital Fatigue in the Workplace: A Systematic Literature Review - Dewi, Suci Permata; Mardi, Mardi; Aminah, Hania (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to conduct a systematic review of the existing literature on digital fatigue in the context of human resource management, focusing on the causative factors and their impact on employee performance and well-being. Digital fatigue refers to mental, physical, and emotional fatigue that arises from excessive exposure to digital technology, such as the constant use of digital devices in daily work. Through a literature search conducted in the Scopus database, a total of 279 articles were identified, and after screening, 116 articles met the criteria for further analysis. Key findings from the review suggest that the main cause of digital fatigue is excessive use of technology, especially related to screen time, virtual meetings, and uncontrolled digital communication. The impact of digital fatigue on employees includes decreased productivity, low engagement, increased stress, and decreased job satisfaction. These findings connect with the Job Demands-Resources (JD-R) theory, which explains how high job demands, such as excessive use of technology, can increase stress and lower performance, while inadequate resources exacerbate the situation. The study also identified gaps in the literature related to organizational policy management strategies to reduce digital fatigue, as well as the need for further longitudinal research to understand its long-term impacts. The practical implications of this study show the importance of managing technology in the workplace and developing policies that support employee well-being in the digital age.